Nutritional marginal zinc deficiency disrupts placental 11β-hydroxysteroid dehydrogenase type 2 modulation - Huang, Y. L. (2016)
This paper investigated if marginal zinc nutrition during gestation could affect fetal exposure to glucocorticoids as a consequence of a deregulation of placental 11βHSD2 expression. Placenta 11β-hydroxysteroid dehydrogenase type 2 (11βHSD2) plays a central role as a barrier protecting the fetus from the deleterious effects of excess maternal glucocorticoids. Rats were fed control (25 μg zinc per g diet) or marginal (10 μg zinc per g diet, MZD) zinc diets from day 0 through day 19 (GD19) of gestation. At GD19, corticosterone concentration in plasma, placenta, and amniotic fluid was similar in both groups. However, protein and mRNA levels of placenta 11βHSD2 were significantly higher (25% and 58%, respectively) in MZD dams than in controls. The main signaling cascades modulating 11βHSD2 expression were assessed. In MZD placentas the activation of ERK1/2 and of the downstream transcription factor Egr-1 was low, while p38 phosphorylation and SP-1-DNA binding were low compared to the controls. These results point to a central role of ERK1/Egr-1 in the regulation of 11βHSD2 expression under the conditions of limited zinc availability. In summary, results show that an increase in placenta 11βHSD2 expression occurs as a consequence of gestational marginal zinc nutrition. This seems to be due to a low tissue zinc-associated deregulation of ERK1/2 rather than to exposure to high maternal glucocorticoid exposure. The deleterious effects on brain development caused by diet-induced marginal zinc deficiency in rats do not seem to be due to fetal exposure to excess glucocorticoids.